Kewenangan Mediator Khusus Ditingkat Daerah Dalam Menyelesaikan Perselisihan Hubungan Industrial - Jonler, Yutson; Nirahua, Salmon Eliazer Marthen; Pattipawae, Dezonda Rosiana (Bacarita Law Journal, 2023)
Appointment of a Special Mediator by the Minister without having to undergo mediator certification, which is an absolute requirement for mediators in general. The purpose of this writing is to find out and analyze the mechanism for appointing and handling industrial relations disputes by Special Mediator as a form of legal protection for disputing parties. The research method is normative juridical. The research results show that the Minister's authority to appoint special mediators at the regional level is in accordance with the mandate of the constitution, however, in this appointment there is an urgent dispensation, namely being exempt from undergoing mediator certification, which is an absolute requirement for mediators in general. The existence of this dispensation will have an impact on special mediators at the regional level in handling industrial relations disputes.